2003
DOI: 10.1034/j.1600-6143.2003.30202.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory BK Virus-Associated Nephropathy With Cidofovir

Abstract: BK virus-associated nephropathy (BKVN) has become recognized as an important cause of allograft dysfunction in renal transplant recipients and despite reduction in immunosuppression, 30-40% of recipients ultimately progress to allograft loss. Cidofovir is an antiviral agent that demonstrates in vitro activity against murine polyomavirus and has been proposed for treatment of BKVN in renal allograft recipients. We describe the clinical course, renal function, serial renal histology and urine and blood viral loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 21 publications
2
100
1
4
Order By: Relevance
“…Biopsy-proven rejection after immunosuppression reduction is reported in up to 25% of patients (29), which compares to 32% seen in the NAPRTCS cohort. Although there have been no controlled trials, antiviral therapy with cidofovir has been reported in cases in which immunosuppression reduction is not sufficient (13,14,30). In our study, cidofovir was used in six (24%) of 25 cases.…”
Section: Discussionmentioning
confidence: 67%
“…Biopsy-proven rejection after immunosuppression reduction is reported in up to 25% of patients (29), which compares to 32% seen in the NAPRTCS cohort. Although there have been no controlled trials, antiviral therapy with cidofovir has been reported in cases in which immunosuppression reduction is not sufficient (13,14,30). In our study, cidofovir was used in six (24%) of 25 cases.…”
Section: Discussionmentioning
confidence: 67%
“…Favorable outcomes have been reported in several cases. [62][63][64] Brincidofovir (CMX001) Brincidofovir (CMX001), an experimental prodrug of cidofovir, has shown antiviral efficacy and a better …”
Section: Cidofovirmentioning
confidence: 99%
“…), hastalar yakından izlenmelidir. [58][59][60][61] Kinolonlar, DNA giraz inhibisyonu yaparak, T hücreler için BKV'ye karşı in vivo ve in vitro aktivite sağlarlar. [62][63][64] İki ay gatifloksasin kullanımı sonrası BKVN gözlenen nakilli hastalarda, viremide ve decoy hücrelerinde azalma olduğu izlenmiştir.…”
Section: Tarama Testleri̇unclassified